Budaya Organisasi, Lingkungan Kerja, Kompensasi dan Kinerja Karyawan di Koperasi Pasar Srinadi Klungkung - Megantari, Ni Putu Maetri; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2021)
The purpose of this study was to obtain empirical evidence of the influence of organizational culture, work environment and compensation on employee performance at the Srinadi Klungkung Market Cooperative. This research was conducted at the Srinadi Klungkung Market Cooperative. The number of samples taken as many as 50 employees accounting and finance section, with non probability sampling method with purposive sampling technique. Data collection is done through a questionnaire. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that organizational culture, work environment and compensation had a positive effect on employee performance. This shows that with a good organizational culture and environment, and giving compensation to employees, employee performance will increase. The results of this study can provide additional information in empirical studies regarding the influence of organizational culture, work environment and compensation on employee performance. Keywords: Organizational Culture; Work Environment; Compensation; Employee Performance.